Sosialisasi Pelatihan Penerapan Website untuk Proses Penerimaan Peserta Didik Baru (PPDB) pada SMK Bina Jaya Palembang - Akhmad Sayuti; Irian Nasri; Robi Krisna; Januari ida Wibowati; Violeta Nirmala; Efniar (Yayasan Pelita Negri Belantaraya, Kab. Indragiri Hilir, Prov. Riau, 2024)
Admission of New Students (PPDB) is an annual routine activity that has a crucial role in determining a school's success in attracting prospective students. Bina Jaya Palembang Vocational School faces challenges in the PPDB process which has been carried out manually, resulting in limitations in time efficiency, data accuracy and information coverage. To overcome this problem, training activities were carried out on implementing the website as an innovative solution to support the PPDB process. This activity aims to introduce and train schools in the use of a website platform specifically developed to simplify the PPDB process. This socialization includes conveying the benefits of using the website, training in technical operations, inputting prospective student data, as well as managing information related to admissions. The training method is carried out through presentation approaches, live demonstrations, and practical sessions by participants. The results of the socialization activities showed an increase in participants' understanding and skills in using the PPDB website. Apart from that, the implementation of this website is expected to increase the efficiency of the new student admission process, expand access to information for prospective students and parents, and create a more transparent and accountable system. The success of this socialization is the first step in digital transformation at SMK Bina Jaya Palembang to face the era of information technology that continues to develop